ABDUCTIVE REASONING ON ETHICS BY MEDICAL STUDENTS USING AN AUDIENCE RESPONSE SYSTEM - Mah KK; Candlish K (Asian Journal of Medicine & Health Sciences, 2019)
Second year medical students were presented with six scenarios, each representing a dilemma in ethics. All of these scenarios were linked to five options, each of which could represent a possible response to the dilemma, and the students were required to choose which one of these they most favoured. A computerized audience response system was used to individualize the procedure and to ensure participation of all students. Subsequently more information was given about the circumstances of each dilemma, and the same set of options was displayed, allowing another round of voting, whereby the students could change their minds if they wished. Then more information was given, and the voting repeated. The aim was to ascertain if providing information in three stages can aid the students in selecting the (undisclosed) responses favoured by the authors. The results indicated that, on the whole, provision of further information within an ethical dilemma does not enhance the students’ ability to discern what is right and proper and that in this group at least more effort must be put into the ethics instruction.